Catalogue of Opiliones (Arachnida) types deposited in the Arachnida and Myriapoda collection of the Instituto Butantan, São Paulo, Brazil - Coronato-Ribeiro, Amanda; Pinto-Da-Rocha, Ricardo; Rheims, Cristina Anne (Zootaxa, 2013)
A catalogue of the Opiliones types of the “Instituto Butantan”, São Paulo, Brazil is given, surveying the collection after severe fire damaged in 2010. Of a total of 91 species with type material listed for the collection, 69 could be located, and 22 are considered lost. The species are arranged according to their families and genera. The collection of Salvador de Toledo Piza Jr., housed at the Museu de Zoologia “Luiz de Queiroz”, was donated to the Instituto Butantan in 2009. These types received a new accession number and are listed under this new affiliation for the first time.